Divergência acústica e morfológica em populações de Allobates femoralis (Anura, Dendrobatidae) do alto Rio Madeira. - Simões, Pedro Ivo (Instituto Nacional de Pesquisas da Amazônia - INPA, 2006)
Since the 19th century, researchers have hypothesized that large Amazonian rivers function as barriers to dispersal. However, case studies using anurans detected no river effect to date in the region. This study aimed to determine the influence of the upper Madeira River on acoustic and morphological divergence patterns in populations of the dart-poison frog Allobates femoralis. Seventeen collecting sites were established in forested areas on both margins of the upper Madeira River, in the Brazilian State of Rondônia, where I recorded the advertisement calls, weights and external morphological variables of E. femoralis males. I encountered two very distinct morphotypes, which probably represent distinct taxa. One, with a 2-note advertisement call, occurs only on the left bank of the upper Madeira River, up to a parapatric contact zone with the second morphotype, where there are presently no apparent barriers to dispersal. The second morphotype, with a 4-note advertisement call, occurs on both sides of the river. Multivariate analysis of variance (MANOVA) showed that, once the effects of body size, air temperature and distances between collecting sites have been removed, there are 3 distinct groups relative to vocalizations and morphology: Group 1: populations belonging to the 2-note call morphotype; Group 2: populations belonging to the 4-note calls morphotype inhabiting the left riverbank; and Group 3: populations belonging to the 4-note calls morphotype inhabiting the right riverbank. Differences between relative finger lengths and body condition among samples of the 4-note morph corroborated those results. We conclude that there is evidence for the upper Madeira River delimiting distinct populations. However, at least one population sample included in the acoustic analysis and another included in the morphological analysis did not correspond to the general divergence pattern, suggesting that the river effect has not been sufficient to result in fixed differences between populations of A. femoralis on opposite riverbanks. Therefore, besides the separation of population by the riverbed, geological features such as a limit between two geo-morphological units found on the left bank, are necessary to explain the vocal and morphological divergence between the A. femoralis morphotypes found in this region.
Keywords: Bioacústica de sapos; opulações de Allobates; Allobates femoralis